2015
DOI: 10.5020/18061230.2015.p337
|View full text |Cite
|
Sign up to set email alerts
|

Ser cuidador de familiar com câncer de cabeça e pescoço

Abstract: RESUMOObjetivo: Conhecer a percepção de cuidadores informais sobre o cuidar de um familiar acometido por neoplasia maligna de cabeça e pescoço. Métodos: Estudo qualitativo realizado no período de março a maio de 2014, no ambulatório de radioterapia do Centro de Alta Complexidade em Oncologia (CACON) do Hospital Universitário de Brasília (HUB)-Brasil, baseado em entrevista semiestruturada com nove cuidadores. Os dados foram submetidos à Análise de Conteúdo, sendo identificadas quatro unidades de significado: "R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
1
3
0
2
Order By: Relevance
“…Similar to other studies, caregivers of head and neck cancer patients are usually women and the patient's spouse, and often have help from another family member. 16 17 In addition, this research also found that having someone to help with patient care decreases the caregiver burden, with better results on the Zarit scale.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Similar to other studies, caregivers of head and neck cancer patients are usually women and the patient's spouse, and often have help from another family member. 16 17 In addition, this research also found that having someone to help with patient care decreases the caregiver burden, with better results on the Zarit scale.…”
Section: Discussionsupporting
confidence: 51%
“…According to Rigoni et al, 17 caregivers had a compromised quality of life, similar to that of the head and neck cancer patient, showing that not only the patient becomes ill, but also his/her caregiver. The burden suffered by the caregiver plays a relevant role in this aspect, as pointed out by Honório et al, 16 with the main altered functions in the caregiver's life being overload and routine change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Observaram ainda que o cuidar de um familiar com câncer interfere diretamente na qualidade de vida dos cuidadores. 13 Revista Ciência & Humanização do Hospital de Clínicas de Passo Fundo -RECHHC Confirmam a religiosidade como uma estratégia central de enfrentamento, considerando que, quando funciona como influência positiva, pode ajudar na aceitação da condição do paciente. Abordam ainda que a família é um agente fundamental no tratamento do paciente com câncer e, portanto, os familiares também devem ser acolhidos nos serviços de saúde, formando uma importante e necessária rede de apoio social ao paciente.…”
Section: Análise E Discussão Dos Resultadosunclassified